Submarine Groundwater and River Discharges Affect Carbon Cycle in a Highly Urbanized and River-Dominated Coastal Area - Wang, Xuejing; Zhang, Yan; Zheng, Chunmiao; Luo, Manhua; Yu, Shengchao; Lu, Meiqing; Li, Hailong (Frontiers in Marine Science, 2021)
Riverine carbon flux to the ocean has been considered in estimating coastal carbon budgets, but submarine groundwater discharge (SGD) has long been ignored. In this paper, the effects of both SGD and river discharges on the carbon cycle were investigated in the Guangdong-HongKong-Macao Greater Bay Area (GBA), a highly urbanized and river-dominated coastal area in China. SGD-derived nitrate (NO3–), dissolved organic carbon (DOC), and dissolved inorganic carbon (DIC) fluxes were estimated using a radium model to be (0.73–16.4) × 108 g/d, (0.60–9.94) × 109 g/d, and (0.77–3.29) × 1010 g/d, respectively. SGD-derived DOC and DIC fluxes are ∼2 times as great as riverine inputs, but SGD-derived NO3– flux is one-fourth of the riverine input. The additional nitrate and carbon inputs can stimulate new primary production, enhance biological pump efficiency, and affect the balance of the carbonate system in marine water. We found that SGD in the studied system is a potential net source of atmospheric CO2 with a flux of 1.46 × 109 g C/d, and river, however, is a potential net sink of atmospheric CO2 with a flux of 3.75 × 109 g C/d during the dry winter season. Two conceptual models were proposed illustrating the major potential processes of the carbon cycle induced by SGD and river discharges. These findings from this study suggested that SGD, as important as rivers, plays a significant role in the carbon cycle and should be considered in carbon budget estimations at regional and global scales future.